Analysis Feasibility of Photovoltaic Array Drive a Medium Temperature Refrigerator - I Dewa Made Cipta Santosa; I Gede Nyoman Suta Waisnawa (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
Solar power (photovoltaic) is one of the clean energies that is very well developed in a tropical country like Indonesia. This is due to the high intensity of the sun and shining throughout the year so that the annual energy obtained is relatively high. The solar energy system in this research was developed with a photovoltaic array system that can be optimized for angles and facing according to where the experiment was carried out. The solar system using Solar Control Charge (SCC) and an inverter in order to get both alternating and direct current output. This energy output from solar power is used to drive the medium temperature refrigerator system for storing fresh vegetables and fruit. The results obtained from this preliminary study are the best angle and direction is an angle of 15 degrees to the north. And this condition will be determined in the form of a fixed tilt on the solar power system located at the Bali State Polytechnic and its surroundings.